Foreign competition in Japan : human resource strategies - Ballon, Robert J. (London ; New York : Routledge, 1992)
This book is divided into three parts: The labour market; The workplace; and The marketplace.
Keywords: Management; Corporations; Commerce; Competition, International; Corporations, Foreign -- Japan -- Personnel management; Japan -- Commerce; Japan -- Commerce